Factors Influencing Incidence of Poverty in Thenmaradchy Division of Jaffna District - Thiruvathany, T.; Sooriyakumar, K.; Sireeranhan, A. (University of Jaffna, 2008)
This paper studies the factors that influence the poverty level of households in Thenmaradchy division of Jaffna district. Thenmaradchy area is highly affected by war. Most of the people in this area lost their houses and other assets. It has serious consequences for the living standard of population in this area. For this study, 150 households were randomly selected by stratified random sample procedure. Because the purpose of study is determine the factors that influence a household to live below the rural poverty line the sample of randomly selected 150 households is considered as sufficient for this econometric analysis. Data was collected from the selected households regarding family size, income sources, expenses and demographic characters. A Probit model was developed to analyze the effect of size of family, income level, home garden, expenses for non-food item, livestock and expenses on liquor on the poverty level of households in the study area. The estimated coefficient for number of family members shows the negative sign as expected but not significant at 5% level. This indicates that having the higher number of family members in a family increase the probability for the poverty. The estimated coefficient for income shows the positive sign as expected and significant at 5% level. The positive sign of income shows that when the income increases the probability for poverty decreases. Estimated coefficient of home garden variable has positive sign as expected and significant at 5% level. It indicates if a family holds home garden, the probability for poverty decreases. The estimated coefficient of having cattle shows positive sign but not significant at 5% level. It indicates that when a family holds cattle the probability for poverty decreases. Estimated coefficient of expenses on non-food item holds a negative sign but not significant at 5% level. When expenses on non-food item increases family reduces expenses on food item. The estimated coefficient for expenses on liquor item shows negative sign but not significant at 5% level. It indicates when the expenses on liquor item increase the probability for poverty increases. Therefore, a better family health planning program, income generating program, encouraging home gardening and rearing livestock, awareness program regarding the side effect of alcohol usage will reduce the incidence of poverty in this region.